ASHABIYAH IBN KHALDUN DAN RELEVANSINYA DENGAN NEGARA INDONESIA PERSFEKTIF SIYASAH SYARIYYAH - Kadir, Nur Asmah; Halimang; Mustarin, Basyira (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
This research aims to analyze Ibn Khaldun's thoughts on Ashabiyah in the state. The problem of this research in that there is dissolidarity in the state because there are differences in ethnicity and religion so that Ibn Khaldun thoughts can provide learning about the importance of Ashabiyah in the state. The research method used is literature (Library Research) with a historical, Islamic and philosophical approach. The research results show that the Ashabiyah concept has an important role in preventing conflict and injustice and maintaining community unity. Ibn Khaldun explained that a country that has a strong asabiyah will be able to create a high human civilization. On the other hand, if the sense of Ashabiyah fades and is only understood narrowly, then there will only be absolute nepotism which will make the country destroyed. The meaning of asabiyah that Khaldun refers to is solidarity and support from the people for the government. The greater the support of the people, the stronger a country will be and vice versa. The Ashabiyah concept assumes that a leader must come from the solidarity of the group (ashabiyah) that is most dominant and plays the most role. According to Ibn Khaldun, a leader mustfulfill 4 requirements for imamate, namely intellectuality, fairness, health and capability.